Comparison of Alum and Poly Aluminium Chloride at Various Doses in Coagulation Process on Color Removal of Palm Oil Mill Effluent (Jurnal Bahan Alam Terbarukan, 2022)
The goal of this study was to investigate the effect of the type and dose of coagulants on the color removal of POME through the coagulation process. The coagulants used in this study were alum and poly aluminium chloride (PAC). The dose of coagulants was varied to 2, 4, 6, and 8 g/L. The results of this study showed that the optimum dose for coagulant of alum was 6 g/L and the optimum dose for coagulant of PAC was 8 g/L, in which these doses resulted in color removal efficiencies of 80.65±10.30% and 94.12±1.00%, respectively. The PAC coagulant was more effective than the alum coagulant. The kinetic models used to predict the color removal efficiencies were the first- and second-order kinetic models. Based on the kinetic analysis, the MAPE of the first and second-order kinetic models was 9.17-28.28% and 5.48-21.62%, respectively. It means that the second-order kinetic model can predict with higher accuracy than the first-order kinetic model. By the second order kinetic model, the reaction kinetic constant of the coagulation process at alum coagulant of 6/L and PAC coagulant of 0.021 and 0.057 /min, respectively.